PEREMPUAN, CINTA, DAN RELIGI DALAM DI BAWAH LINDUNGAN KA’BAH KARYA HAMKA: KEBERAKSARAAN DAN KELISANAN - Inung Setyami; Irma Satriani (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
Film is the result of the culture of high-tech society that is presented through audio-visuals. many blockbusters whose screenplays are adaptations or inspirations from literary works. One example of the many literary works that have been multimediaized is the novel Di Bawah Lindungan Ka’ bah (DBLK). This study aims to describe the representation of women, love, and religion in Hamka's novel DBLK. in terms of literacy and orality both. The research data source is the novel DBLK by Hamka. The DBLK novel was first published by the publisher Bulan Bintang in 1938. The type of research is descriptive qualitative research. The method used is the method of listening, reading, recording and comparison. The results of the study show that 1) the media has made a diversion. The transfers made by the media in the DBLK novel into film form, namely the transfer of images of women, love, and religion. 2) There is an overlap between orality and literacy, namely the dialogues presented by the characters in the film are literacy from the novel. In visualizing the novel into a DBLK film as a second oral form, it still relies on the use of characters to refer to when (year) and where (place).